Immune Microenvironment in Langerhans Cell Histiocytosis: Potential Prognostic Indicators - Feng, Chuchu; Li, Yang; Ke, Huang; Peng, Xiaomin; Guo, Haixia; Zhan, Liping; Xiong, Xilin; Weng, Wenjun; Li, Jiaqiang; Fang, Jianpei (Frontiers in Oncology, 2021)
In this study, the immune microenvironment in Langerhans cell histiocytosis (LCH) was characterized to determine if immune indices are predictive of severity. Serum samples from 54 treatment-naïve patients were analyzed quantitatively for inflammatory cytokines and immunoglobulins before and after the induction of chemotherapy. The initial serum sIL-2R, TNF-α, and IL-10 of untreated LCH patients with risk organ involvement (RO+) were significantly higher than those with single-system (SS) involvement. LCH patients with hematologic involvement exhibited a significantly higher sIL-2R, TNF-α, IL-10 and IL-1β expression, as compared to the group without involvement. sIL-2R, TNF-α and IL-10 were increased in patients with liver or spleen involvement. Th cells have decreased in the liver+ and spleen+ group, and Ts cells were significantly decreased in non-response group after induction chemotherapy. The serum level of immune indices represents, to some extent, the severity of the disease. Pertinent laboratory inspections can be used to improve risk-stratification and guide immunotherapy.